Study of the Deactivation of ß-galactosidase Entrapped in Alginate-carrageenan Gels - Mammarella, Enrique José (2005)
The stability of ß-galactosidase entrapped in Ca-alginate–K-k-carrageenan gels under operation conditions was studied. The thermal deactivation of the immobilised enzyme and the biocatalyst protein loss due to gel swelling were taken into account in the mass balance of the enzymatic reaction rate expression. Time-temperature effect was the most important factor in the biocatalyst deactivation reaction. However, results showed that the enzyme entrapped in gels was partially lost by gel swelling, which was a source of error in predicting results in continuous processes. The enzyme loss determined in this work showed a non-linear behaviour and it depended on mixing conditions of the reactor. Values of protein loss were used in the modelling of a fixed-bed reactor with similar flow conditions to reduce the error in predicting the operation conditions to maintain a constant conversion. For reaction conditions similar to those analysed in this work, the ß-galactosidase was well entrapped in alginate-carrageenan matrices.